DEVELOPING A NUMERACY DIAGNOSTIC ASSESSMENT MODULE FOR EARLY PRIMARY SCHOOLERS POST COVID-19 PANDEMIC - Barumbun, Mardyanto; Salim S, Soma; Bua, Mety Toding; Ramadhani, Thea (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2023)
School closures due to the COVID-19 pandemic has resulted in learning loss in primary students, so a diagnosis of the students' numeracy skills is urgently needed at the beginning of learning to adapt learning to students' average ability levels (teaching at the right levels). This study aims to develop a module that can assist and become a reference for teachers in schools in diagnosing and mapping students' numeracy abilities at the beginning of learning. This research was carried out following the procedures for research and development (R&D). The developed module was validated by two experts (media and material experts) prior to implementation with the validation results being in very good categories for each aspect of the material, layout, and graphics. The results of the study based on the teacher's response questionnaire indicated that the module developed is very helpful for the teachers in mapping students' numeracy abilities at the beginning of learning after the COVID-19 pandemic, and it provides an alternative follow-up to the results of students' numeracy assessments. Thus, the developed module is suitable for use as a reference in conducting assessments regarding early primary school students’ numeracy skills.